URBANIZATION AND LAND USE CHANGE: A GEOGRAPHICAL ANALYSIS OF JAIPUR CITY - Saini, Rekha (International Journal of Research -GRANTHAALAYAH, 2025)
Urbanization has become a rapid and irreversible process in the present era. Especially in developing countries like India, urbanization has had a profound impact not only on the population structure but also on the land use pattern. Jaipur city, the capital of Rajasthan, is a historic and rapidly developing city, which has witnessed a rapid increase in population and construction activities in the past decades. This change has changed the traditional land use pattern and created a situation of environmental imbalance. This study will analyze the trends of urbanization and the land use changes resulting from it, especially in the context of a historic and planned city like Jaipur city. This research will highlight the socio-economic impacts, environmental consequences and challenges associated with urban planning of this process, as well as propose possible solutions for sustainable urban development.